An Examination of Women's Sports Coverage on the Twitter Accounts of Local Television Sports Broadcasters. (August 2017) - Hull, Kevin
This study examines the amount of coverage given to women's sports by local television sports broadcasters on Twitter. A total of 19, 649 tweets from 201 local sports broadcasters throughout the United States were examined using content analytic methods during a constructed 2-week period. Results demonstrated that while a majority of the local sports broadcasters did tweet about women's sports, these tweets represented only about 5% of the overall number of messages. Further examination demonstrates that female sports broadcasters tweeted about women's sports less frequently than male sports broadcasters did. Additionally, broadcasters in smaller cities were more likely to report about women's sports than those in larger cities. While results are consistent with previous research on gender representation on nationally televised highlight shows, these findings are significant because they demonstrate that there is a relationship between gender of broadcaster and market size in relation to the number of tweets about women's sports. Additionally, data are from Twitter, in which there are no time constraints that would seemingly limit the amount of women's sports that could be mentioned by a sportscaster.